Anisotropy of Magnetic Susceptibility Reveals Late Miocene Tectonic Activity in the Western Qaidam Basin - Zhang, Weilin; Li, Bingshuai; Yan, Maodu (Frontiers in Earth Science, 2022)
The western Qaidam Basin on the northeastern Tibetan Plateau located at the intersection between the Altyn Tagh Fault and the Kunlun Fault/Qimen Tagh Fault holds significant potential to reveal the tectonic process of these two faults as well as the evolution of the Qaidam Basin. In this paper, we conducted detailed anisotropy of magnetic susceptibility (AMS) records from Late Cenozoic sediments at the Qigequan section in the western Qaidam Basin to shed new light on the tectonic processes in this region. Based on the distribution of three principal axes of magnetic fabrics as well as magnetic fabric parameters, the AMS records can be divided into three parts. The lower part (∼6.9–4.6 Ma), mainly made of fine-grained mudstone and siltstone, exhibits three well-grouped principal axes with a NE-SW elongated Kmin axis as the embryonic tectonic magnetic fabric, suggesting constant NE-SW compressional strain. The middle part (∼4.6–3.0 Ma), characterized by mudstone, siltstone and sandstone, shows three less grouped principal axes and suggests a relatively weak and stable tectonic environment. The three principal axes of the upper part (∼2.4–0.4 Ma) is composed of sandstone and conglomerate of the Qigequan Formation, similar to the middle part, which was primarily attributed to the coarse lithology and not sensitive to tectonics since ∼2.6 Ma. The NE-SW compressional strain in the western Qaidam Basin is consistent with that in the northeastern basin, both of which are parallel to the upper crust movements revealed by the GPS, suggesting the dominant NE-SW compressional strain in the western and northern basins in the late Cenozoic. The decreasing magnitude of tectonic activities during ∼6.9–4.6 Ma indicates that the major geological units released most of the compressional strain in the western Qaidam Basin during tectonic activity that initiated in the early-late Miocene.